Pengaruh Motivasi Kerja, Kepuasan Kerja dan Lingkungan Kerja Terhadap Loyalitas Karyawan PT Cimb Niaga - Naufal Azrial Darmawan (Journal of Management and Social Sciences, 2025)
Every organization needs to have the right strategy to survive in carrying out its operational activities. Employee loyalty has attracted much attention because it is the expectation that motivated and loyal employees will act in the best interests of the organization. This research aims to determine the influence of work motivation, job satisfaction, and work environment on employee loyalty at CIMB Niaga Bank, South Jakarta. The respondents for this research were 125 respondents with criteria based on gender aged 17 - 55 who worked at CIMB Niaga Bank, South Jakarta in the last 3 months. The analysis method used is Multiple Linear Regression. The research results parcial show that work motivation has a significant effect on employee loyalty, job satisfaction has a significant effect on employee loyalty and the work environment has no effect on employee loyalty. Then simultaneously work motivation, job satisfaction and work environment have a significant effect on employee loyalty.